Design Guidelines Of Motorcycle Riders In Bandung Indonesia - Dandi, Yunidar (2022)
This study was conducted based on the belief that people are interested in anything that looks and feels attractive, colorful, and fun, they are also unique individuals with different personality traits, therefore the traits influence their preference, reaction, and behavior toward a product.